Using the new media to enhance the learning process for adult learners - Awang Abu Bakar, Normi Sham (2011)
The emergence of the new digital media has influenced how learners of the institute of higher learning perceive their learning experience. Instead of depending on books and printed materials alone, they have taken education to a new level, where knowledge seeking now involves the digital media and many other types of technology. This paper highlights several types of new media which have proven to be very effective in enhancing the learning process of adult learners in higher education. The digital age has reshaped our education system to be more learner- centred, to encourage self-discovery, to customize course content, and to promote collaborative learning. This can be achieved by bringing forward various kinds of new media such as audio visual technology in the forms of coursewares and podcasts, and also using the internet, especially the latest development of Web 2.0 technology which includes Skype, blogs, YouTube, Wikis, Facebook and MySpace. These technologies have contributed towards providing lifelong learning to the learners.